Study of Physical and Mineral Properties of Soil Clay Landslide Location of IAIN Campus Ambon City - Luhukay , Marcus; Risamasu, Robby G.; Osok, Rafael M; Slamet, Sonya (Future Science / FSH-PH Publications, 2022)
This study aims to determine physical and clay mineral properties of soils and how they affect the occurrence of erosion in the IAIN Campus Ambon. The results indicated that the two soil profiles shows a variety in soil properties. the largest distribution of soil particle density is 2.63 at soil layer P2L3 and the smallest is 2.26 at P1L1, the largest soil pore distribution is 60.12% at P2L1 and the smallest is 29.36% at P1L3, while the largest soil pores ratio distribution is 1.51% at P2L1 and the smallest is 0.42% at soil layer P1L3. The soil porosity reflects the level of the soil ability to pass water flow (permeability) or the speed of water flow to pass through the soil mass (percolation). By the decreasing of soil porosity and pore ratio in layers 3 and 4, the permeability is also slower. The major clay mineral found in both soil profiles is kaolinite, an unwell consolidated secondary clay mineral type 1:1 mixed with quartz, the most weathering resistant primary minerals. These two minerals have lower friction resistance due to the increasing of clay content in the lower soil profiles. The physical and hydrological soil properties as well as the presence of kaolinite and quartz in the lower soil layers are considered to be the cause of the erosion occurrence in the study area (IAIN campus).